The complete poems of Paul Laurence Dunbar - Dunbar, Paul Laurence, 1872-1906 (Dodd, Mead and Co, 1913)
"Dunbar is the first American Negro of pure African bloodto reveal innate distinction in literature; as W.D. Howells has said, to feel the Negro life esthetically and express it lyrically."